1932
DOI: 10.1152/ajplegacy.1932.99.3.534
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Circulation

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

1934
1934
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(34 citation statements)
references
References 0 publications
1
32
0
1
Order By: Relevance
“…Kety and Schmidt, 10 Scheinberg and Stead, 17 Bernsmeier and Siemons, 18 and Lassen, 19 with their inert gas diffusion methods, have obtained mean values of about 50 to 65 ml./lOO Gm. of brain.…”
Section: Velocity Of Circulation In the Brainmentioning
confidence: 98%
See 1 more Smart Citation
“…Kety and Schmidt, 10 Scheinberg and Stead, 17 Bernsmeier and Siemons, 18 and Lassen, 19 with their inert gas diffusion methods, have obtained mean values of about 50 to 65 ml./lOO Gm. of brain.…”
Section: Velocity Of Circulation In the Brainmentioning
confidence: 98%
“…The mathematical derivation of the equations can be found in an article by B. J. Andersson. 9 The equations are generalizations of a formula given earlier by Hamilton et al 10 The second method utilized the concentration curves obtained from samples taken from one carotid artery and the two bulbs after an intravenous injection was made. The formula is correct provided all the inflows show the same concentration curve and all the outflows show the same concentration curve.…”
mentioning
confidence: 99%
“…As previously mentioned, rather than using all the data points obtained, we have restricted our data-fitting to the initial time points of the first pass and analyzed the SI time curve using a mathematical equation based on indicator dilution theory (29) for calculating inverse mean transit time which is equal to the average time it takes any given particle of contrast agent to pass through the tissue. Mean transit time has been utilized previously with other, non-MR methods; for example, Rutishauser et al (30) calculated coronary blood flow by densitometrically determining mean transit time of the contrast medium through the arterial segment of interest.…”
Section: Calculation Of the Mbf Indexmentioning
confidence: 99%
“…These findings accorded well with the sparse data then available (Hickam and Cargill. 1948;Riley et al, 1948;Dexter et al, 1951), and subsequent studies by other workers, I am pleased to say, have also shown remarkable agreement (Freedman et al, 1955 (Hamilton et al, 1932). Yet (Fig.…”
Section: Cardiac Output At Rest and On Exercisementioning
confidence: 59%